BUNGA MELATI SEBAGAI OBJEK LUKISAN BERCORAK REALIS KONTEMPORER - Nining Yuningsih; Erfahmi .; Muzni Ramanto (Serupa The Journal of Art Education, 2012)
Abstract The purpose of this paper is to akhrir jasmine object of beauty can be enjoyed by anyone. The beauty of the scent of jasmine flowers that typically creates a quiet and comfortable atmosphere leads the mind to imagine the ideas lead. Form a picture of jasmine flowers are packed in a painting titled: 1). The girl Minang, 2). Options In Life, 3). Entertaining, 4). Waiting for morning, 5). In the darkness, 6). Jasmine White Purple, 7). Sepi, 8). Fading, 9). Sincerity, 10). Seek the Light. In the painting work better writer to create beauty and advantages of jasmine flowers with bercorakan style "Contemporary Realist", which can describe the form of a realist that is free, and create new forms and contemporary issues raised by the technical and creative concepts.   Kata kunci: Melati, lukisan, realis, kontemporer